The Effect of the SQ3R (Survey, Question, Read, Recite, Review) Learning Model with the Word Square Game on the Intensive Reading Ability of Fourth-Grade Students at MIT Meunara Baro - Jihan Nabilah; Yuni Setia Ningsih; Rafidhah Hanum; Ridhwan M Daud; Saslfayasna Putri Arita (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
Intensive reading is a fundamental skill fourth-grade students must master in Indonesian language learning, as it requires an in-depth understanding of a text's meaning rather than mere word recitation. However, field observations at MIT Meunara Baro show that students' intensive reading ability remains low, with most students' scores falling below the minimum mastery criterion (KKM). This problem is presumably caused by instruction that remains conventional, in which teachers simply hand out a reading text and have students directly answer questions without a systematic reading process, leaving students passive and under-trained in constructing deep meaning from texts. This gap between the demands of intensive reading competence and actual conditions in the field is what underlies the need for an alternative learning model. This study examined the effect of the SQ3R (Survey, Question, Read, Recite, Review) model combined with the Word Square game on intensive reading ability, using a quasi-experimental Nonequivalent Control Group Design (experimental n = 11; control n = 13). The Welch t-test showed the experimental group's posttest mean (88.18) was higher than the control group's (43.46), Sig. (2-tailed) < 0.001, with a very large effect size (Cohen's d = 4.60), confirming a significant effect.